2019
DOI: 10.15252/emmm.201810218
|View full text |Cite
|
Sign up to set email alerts
|

The first steps in vision: cell types, circuits, and repair

Abstract: Dysfunction of the key sense of vision, leading to visual handicap or blindness, has a crucial effect on day‐to‐day life. In this commentary, I will summarize the work in my laboratory that is focused on a basic understanding of visual processing and the use of this information to understand disease mechanism and to develop correcting therapies. We are beginning to understand how cell types of the visual system interact in local circuits and compute visual information. This has brought insight into mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This disrupts axogenesis, dendritogenesis, and neuronal guidance in brain areas involved in the control of eye movement ( 30 ). FRMD7 promoted neurite elongation by modulating actin cytoskeleton whereas FRMD7 gene knockdown led to a significant reduction in overall neurite length ( 34 , 38 ), further contributing to the development of neuronal circuit asymmetry and neurological disorders ( 28 , 39 ). Mutations associated with ICN include missense mutations, null mutations, deletions and insertions, and frameshift mutations.…”
Section: Discussionmentioning
confidence: 99%
“…This disrupts axogenesis, dendritogenesis, and neuronal guidance in brain areas involved in the control of eye movement ( 30 ). FRMD7 promoted neurite elongation by modulating actin cytoskeleton whereas FRMD7 gene knockdown led to a significant reduction in overall neurite length ( 34 , 38 ), further contributing to the development of neuronal circuit asymmetry and neurological disorders ( 28 , 39 ). Mutations associated with ICN include missense mutations, null mutations, deletions and insertions, and frameshift mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an AAV viral capsid that penetrates the primate retina (Byrne et al, 2020) and could be developed for use in human gene transfer experiments was identified. Several excellent reviews describe other aspects of gene therapy in the eye (Cideciyan and Jacobson, 2019;Roska, 2019;Roska and Sahel, 2018).…”
Section: Genetic Methods To Rescue Visionmentioning
confidence: 99%
“…Similarly, an AAV viral capsid that penetrates the primate retina ( 155 ) and could be developed for use in human gene transfer experiments was identified. Several excellent reviews describe other aspects of gene therapy in the eye ( 12 , 156 , 157 ).
Figure 5 Pharmacological intervention using genetic methods.
…”
Section: Genetic Methods To Rescue Visionmentioning
confidence: 99%